KAJIAN PENCEMARAN LINGKUNGAN DI TAMBAK UDANG DELTA MAHAKAM - Salahuddin, Chafid Fandeli, dan Eko Sugiharto (Jurnal Teknosains, 2012)
well-managed, it will contribute to the improvement of both regional and national economy. However, MahakamRiver gets liquid waste pollution that has significant impact on water quality and results in conflicts betweenthe local societies, especially the shrimp pond farmers and the fishermen and the oil and gas industrial company.This research uses descriptive-comparative analysis with ANOVA test to compare samples (water, soil/sediment,shrimp, and mangrove) of the shrimp fishpond (many mangrove, moderate mangrove, few mangrove, and withoutany mangrove). The pollution load which is analyzed includes: cadmium content (Cd), lead (Pb), oil and grease (O& G), mercury (Hg), and arsenic (As). The significance level is 90% with error of 5% (0.05).The water of Mahakam Delta is still in the normality limit as seen from the maximum pollution load in the Decreeof the Minister of Living Environment No. 51 of 2004 on Ocean Water Standard seen from chemical, physical,and biological parameters. The presence of mangrove contributes positive value to the balance of the quality of thewaters and to the neutralizing of heavy metals contents of Mahakam Delta as shown in the average difference inthe Pb, Cd, O & G, As and Hg of the samples of water, soils/sediment, shrimp and mangrove which are drawnfrom the of shrimp pond with many mangrove, moderate mangrove, few mangrove and without any mangrove,which is significantly different (p < 0.05). Shrimp pond with many mangrove has less average levels of Pb, Cd, M& L, As and Hg compared with the pond with less and without mangrove. The shrimp pond with many mangrovescontributes significantly and positively to the prevention of the pollution of Pb, Cd, O and G, As and Hg at low level